Quality of cervical cancer screening in Brazil: external assessment of the PMAQ - Mara Rejane Barroso Barcelos; Rita de Cássia Duarte Lima; Elaine Tomasi; Bruno Pereira Nunes; Suele Manjourany Silva Duro; Luiz Augusto Facchini
ABSTRACT OBJECTIVE To examine whether demographic and socioeconomic variables and the variables of the organization of services are associated with the quality of cervical cancer screening. METHODS This is a survey carried out in the health services of the five Brazilian regions in 2012. The sample consisted of users of basic health units participating in the Program for Improving Access and Quality of the Primary Care. The independent variables analyzed were: socioeconomic characteristics (municipal context), demographic characteristics (user profile), and two domains related to the organization of basic services (work structure and process). The low quality of the screening was assessed from the lack of access, late examination, and lack of guidance. Crude and adjusted analyses by Poisson regression assessed the association between outcomes and independent variables. RESULTS The values of lack of access, late examination, and lack of guidance were 6.7%, 11.2%, and 19.2%, respectively. Problems of quality were lower according to the increase in Municipal Human Development Index and per capita household income, increasing with population size and municipal coverage of the Family Health Strategy. The Midwest region of the country presented the highest occurrences of low quality outcomes. Indigenous and yellow women had the highest prevalence of outcomes. Women with partner, who received the Bolsa Família Program, and who had paid work had less chances of having lack of access, late examination, and lack of guidance. The appropriate work process in health services decreased the likelihood of low quality in all indicators. CONCLUSIONS Investments in the work process of health teams, social cash transfer programs, and social conditions of the population are essential to improve the quality of the program of cervical cancer screening in Brazil.